I Am Still With You: Dementia and the Christian Wayfarer - Kinghorn, Warren A. (Journal of religion, spirituality & aging, 2016)
Persons with dementia suffer not only from neuropathology but also from cultural norms that exalt agency, privilege rationality, equate worth with capacity, and discourage disability and dependence. In Christian theological context, however, these are faulty assumptions that harm people with dementia. Christian tradition affirms, rather, that humans are integrated, whole-person, embodied souls on a journey to God; dependent on others and on God; and endowed by God with intrinsic worth that is unrelated to capacities. Four theological parameterscreation, participation, lament, and songenable resistance to prevalent toxic social norms and promote faithful Christian re-membering of people with dementia.